Relevance of Bharata Muni’s Natyashastra in Digital Era - Gautam, Kedar Nath (Bodhi: An Interdisciplinary Journal, 2024)
This article examines the relevance of Bharata Muni’s Natyashastra in the digital era through qualitative methods such as textual analysis and interpretation. It investigates Natyashastra’s principles, theories, and concepts, assessing their applicability to modern digital communication, content creation, and effective presentation. Using primary sources like translated Nepali texts, previous research works, and secondary scholarly interpretations, the study highlights parallels between Natyashastra and contemporary digital practices. Natyashastra, a foundational text for performing arts, communication, and human behavior, provides comprehensive guidelines on philosophical, spiritual, emotional, and technical expression. It emphasizes the emotional essence (Rasa) and the art of expression (Abhinaya), which are crucial for digital communication. By exploring theatrical elements and holistic storytelling techniques, Natyashastra can inspire innovative digital content production and presentation, enhancing authenticity and engagement. This article underscores the enduring significance of Natyashastra, enriching modern communication and artistic practices, and fostering deeper connections with audiences in the digital landscape.